Childhood cancer, age at diagnosis and educational attainment: A meta-analysis. (January 2020) - Gummersall, Timothy; Skaczkowski, Gemma; Wilson, Carlene
Highlights: Childhood cancer survivors achieve lower final educational attainment than controls. Survivors of central nervous system cancers are particularly disadvantaged. Early age at diagnosis reduces the likelihood of high school graduation. Different outcomes evident in population registry versus self-report studies. Abstract: Despite improved mortality rates, cognitive and academic difficulties are evident in some childhood cancer survivor groups. This meta-analysis aims to determine whether: 1) survivors have lower educational attainment than non-cancer controls; 2) educational attainment varies according to cancer type (CNS versus non-CNS); and 3) whether an early age of diagnosis confers greater disadvantage. A systematic search utilising the terms "neoplasms", "childhood", "educational attainment" and other related terms retrieved 2256 records from Embase, Medline and PsycINFO. Eleven studies satisfied the inclusion criteria. Survivors were less likely than controls to graduate from high school ( OR  = 0.74, 95 % CI: [0.60; 0.92]) or university ( OR  = 0.74, 95 % CI: [0.58; 0.94]). Although educational attainment in survivors of CNS cancer is reduced, non-CNS cancer survivors tend to attain similar educational status to controls. Additionally, there is some evidence that a diagnosis prior to adolescence may reduce the likelihood of high school, but not university, graduation.